Tide and storm surge observations in the Chukchi Sea - Hunkins, Kenneth L. (Kenneth Leland), 1928- (Lamont Geological Laboratory, Columbia University, 1963)
Sea level heights were recorded with a tide gauge at Fletcher's Ice Island (T-3) while it was aground in the Chukchi Sea at 71:55 N, 160:20 W. Harmonic analyses were made for the tidal components. The tidal hour for M sub 2 is 9.11 at this location, in good agreement with the co-tidal chart of Sverdrup (1926). Storm surges observed at this location on the continental shelf have a range of about 40 cm. During relatively stationary atmospheric co-ions, the storm surge heights can be interpreted as due to the static water barometer effect. Dur ing conditions of moving atmospheric pressure systems, storm surge heights differ from those predicted by the water barometer effect. The combined application of Ekman's wind-driven current theory and Bernoulli's equation provides an explanation for these differences. (Author).